Distributed and parallel processing for the embgrid project - Sanz, Cecilia (2002)
The goal of EMBgrid is to overcome relevant infrastructure needs in Bioinformatics development and services in order to address future needs for the provision of useful Bioinformatics solutions to the Biosciences community. The proposed approach will make use of an extended Grid architecture, built on top of existing EU-DATAGRID services and deployed over a wide number of European nodes, to enable delivery of advanced tools and solutions to the growing demands of Biosciences. We contemplate creation of a pan-european Grid resource, related to other EU Grid initiatives and devoted mainly to Bioinformatics. This initiative will raise Europe's competitiveness in this and related fields. Successful deployment and dissemination will be facilitated by EMBnet long track in delivering tools, services and training to the European scientific community.